GAMIFIKASI EDUKASI ANEMIA MELALUI KARTU PRIMA PADA SISWA SMP MUHAMMADIYAH II PAKISAJI, KABUPATEN MALANG - Owen, Elbert; Nadhiva, Farrah Amira; Bialangi, Astriandari; Puspitasari, Diah Ayu; Apriah, Neni Nur; Pratiwi, Zahra Anggita (Darussalam Nutrition Journal, 2025)
Background: Anemia is a global health problem that occurs in adolescent girls with a prevalence in Indonesia reaching 22.6% in 2023. Knowledge about anemia among adolescent girls is still considered low, with compliance to iron supplement tablet (TTD) consumption only at 74%. Objective: This study aims to explore the effectiveness of the PRIMA program (Adolescent Girls Anti-Anemia Program), which applies a gamification approach in nutrition education using card games to improve knowledge about anemia and TTD consumption among adolescent girls.Methods: This quantitative study used a One Group Pre-Test and Post-Test design involving 21 female students from SMP Muhammadiyah II Pakisaji, including grades VII, VIII, and XI, using total sampling technique. Data were collected through a knowledge questionnaire about anemia consisting of 22 questions (out of 22 questions, 14 met validity criteria with a value of 0.6 and reliability with a value of 0.763), anthropometric measurements, and clinical signs of anemia examination. Data analysis was conducted using validity and reliability tests, Shapiro-Wilk normality test, and paired sample t-test.Results: The t-test results showed p<0.05, indicating a significant increase in knowledge after the education intervention. Conclusion: The PRIMA program successfully increased students' knowledge about anemia significantly through a gamification approach, although compliance with TTD consumption remained low due to unpleasant taste and nausea effects.